2009
DOI: 10.1097/nrl.0b013e3181906fc9
|View full text |Cite
|
Sign up to set email alerts
|

Headaches in the Different Phases of Relapsing-Remitting Multiple Sclerosis

Abstract: The high frequency of PSHs in relapse was notable, and, to the best of our knowledge, PSH was not reported in relapsing-remitting multiple sclerosis before. Further studies with larger samples are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
(25 reference statements)
2
25
0
2
Order By: Relevance
“…13 Another study has correlated primary stabbing headaches with the relapse phase of relapsing-remitting MS, implicating stabbing pain as a potential sign of acute demyelination. 14 The pain described by the patients in our study varied based on headache frequency, history, and MS progression. Patients who had a long or frequent history of headaches were more likely to report their pain as throb-Fortunately, for some the incidence of headache may be reduced using a multidisciplinary treatment approach.…”
Section: Impact On Daily Functionmentioning
confidence: 79%
“…13 Another study has correlated primary stabbing headaches with the relapse phase of relapsing-remitting MS, implicating stabbing pain as a potential sign of acute demyelination. 14 The pain described by the patients in our study varied based on headache frequency, history, and MS progression. Patients who had a long or frequent history of headaches were more likely to report their pain as throb-Fortunately, for some the incidence of headache may be reduced using a multidisciplinary treatment approach.…”
Section: Impact On Daily Functionmentioning
confidence: 79%
“…Moreover, although some studies showed that RRMS could be correlated with migraines, this issue could not be confirmed with other studies (3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In another study, it was suggested that deregulation of the serotonergic system may also be involved in the pathogenesis of MS as well as migraines (13).…”
Section: Introductionmentioning
confidence: 88%
“…Initial and relapse symptoms of MS may include acute brachial pain, sore throat, hypoglossal nerve palsy, epileptic seizures, and headache. It is known that headache is very common in patients with MS [1,2,3]. However, there are few studies evaluating headache as a presenting symptom or a predictor of a MS attack [4].…”
Section: Introductionmentioning
confidence: 99%